(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
This article presents the community veterinary pharmacy extension project: you learn through play at an elementary school in Belém-PA, in 2022/2023. The general objective was to promote, through interactive and playful activities, children’s awareness of the dangers of self-medication in animals. The activities were developed by veterinary medicine students from the Federal Rural University of the Amazon-UFRA. The information was compiled in spreadsheets using the Microsoft® world and subjected to quantitative analysis, in absolute and relative frequency. The school collaborated in carrying out the activities, allowing the teaching staff to be involved in the project proposals. The results demonstrated that the activities renewed by the project at the children’s school allowed students to demonstrate their experiences and understanding of the topic, through interactive activities.